2017
DOI: 10.1038/s41598-017-02986-5
|View full text |Cite
|
Sign up to set email alerts
|

Atomistic Corrective Scheme for Supercell Density Functional Theory Calculations of Charged Defects

Abstract: A new method to correct formation energies of charged defects obtained by supercell density-functional calculations is presented and applied to bulk, surface, and low-dimensional systems. The method relies on atomistic models and a polarizable force field to describe a material system and its dielectric properties. The polarizable force field is based on a minimal set of fitting parameters, it accounts for the dielectric screening arising from ions and electrons separately, and it can be easily implemented in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…This change in the screening is the cause for the two length scales. One could then fit only the energies in the weak screening regime with a low-order polynomial, if such large supercells are computationally tractable [3]. Alternatively, we found that the energies can be well fitted in both regimes when the second-order polynomial is appended with an exponential term:…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…This change in the screening is the cause for the two length scales. One could then fit only the energies in the weak screening regime with a low-order polynomial, if such large supercells are computationally tractable [3]. Alternatively, we found that the energies can be well fitted in both regimes when the second-order polynomial is appended with an exponential term:…”
mentioning
confidence: 95%
“…This issue was first pointed out by Noh et al [1] (and later on reported at least in Refs. [2,3]), who suggested using a fifth-order polynomial for the fitting.…”
mentioning
confidence: 99%
“…As a consequence, the unit cell carries an electric dipole, while the shape of the associated field is a modeling artifact. In the literature, two methods have been proposed to compensate for this: (i) extrapolation to the dilute limit by finite-size scaling [29] and (ii) a posteriori corrections based on dielectric models [30][31][32].…”
Section: Jellium Modelmentioning
confidence: 99%
“…As a consequence, the unit cell carries an electric dipole, while the shape of the associated field is a modeling artifact In the literature, two methods have been proposed to compensate for this: (i) extrapolation to the dilute limit by finitesize scaling 19 (ii) a posteriori corrections based on dielectric models [20][21][22] .…”
Section: Models For Metal Substratementioning
confidence: 99%